Life-as-Lived Today: Perpetual (Undesired) Liminality of the Half-widows of Kashmir - DSouza, Paul (Culture Unbound, 2016)
According to Victor Turner, all liminality must eventually dissolve, for it is a state of great intensity that cannot exist very long without some sort of structure to stabilize it. This paper takes his lead and attempts to describe the liminal status of those women, the whereabouts of whose husbands are not known (they are locally referred to as ‘half-widows’) in the conflict zone of Kashmir, India. The article examines the concept of liminality based on life as lived today by these half-widows and shows how the effects of liminality operate in their day to day life, making them extremely vulnerable victims. In this, it is an attempt to expand upon the concept of liminality, originally linked almost exclusively to rites of passage. Furthermore, this paper reflects on the idea of permanent liminality that has been elaborated by sociologist Arpad Szakolczai. The narratives of the half-widows of Kashmir provide an example of how they are trapped in a form of “permanent liminality” far beyond what was initially defined as a “temporal state”.